EFFECTS OF DIETARY THIAMINE SUPPLEMENTATION ON PERFORMANCE, EGG QUALITY, AND ANTIOXIDANT-RELATED ENZYMES IN CHINESE EGG-LAYING - W. Chen; A. M. Fouad; D. Ruan; S. Wang; W.G Xia; C. T. Zheng (Journal of Animal and Plant Sciences, 2018)
Thiamine, or vitamin B1, is an important water soluble vitamin in poultry nutrition due to its central role in the metabolism. Thus an experiment was designed to investigate the effects of dietary thiamine supplementation on performance, egg quality, and antioxidant-related enzymes in laying ducks. In total, 900 Longyan pullets 22wk-old with similar body weight were randomly assigned to six treatments (twenty five ducks per replicate pens and six replicates per treatment). The control group was fed a corn-soybean meal basal diet containing 0.93 mg thiamine/kg, while the other treatment groups were fed basal diets supplemented with 1.0, 2.0, 3.0, 4.0, or 5.0 mg thiamine/kg. The experimental data were analysed by one-way ANOVA as a single factor design. Dietary thiamine did not change egg production, egg weight, egg mass, FCR, shape index, Haugh unit, yolk color, egg composition, eggshell quality, and concentrations of antioxidant-related enzymes, but it elevated (linearly; P< 0.02) the lipid peroxidation. These findings indicate that corn- soybean meal diet could cover thiamine needs for Longyan egg-laying ducks at 22 to 42 wk of age. define thiamine requirements for egg-type ducks. To the
Keywords: Thiamine; laying ducks; lipid peroxidation.